Modern polygamy in the United States: historical, cultural, and legal issues - Jacobson, Cardell K.; Burton, Lara (Oxford University Press, 2011)
"This well-balanced collection by historians, social scientists, and legal scholars, most of them established experts, provides a comprehensive treatment of the FLDS and other contemporary polygamous cultures in North America. The authors examine religious and other rationales for this way of life that are offered by both male and female participants, and present candid critiques both of the polygamous communities and of their antagonists in law enforcement and in the mass media."--Armand L. Mauss, author of The Angel and the Beehive: The Mormon Struggle with Assimilation